KOMUNIKASI BERMEDIA: PENGELOLAAN PESAN OLEH PENULIS SUNDA DI KOTA BANDUNG: KOMUNIKASI BERMEDIA: PENGELOLAAN PESAN OLEH PENULIS SUNDA DI KOTA BANDUNG - Santi Susanti; Wahyu Gunawan (Jurnal Kajian Budaya dan Humaniora, 2024)
Information conveyed in writing has the power to influence its audience so that writers must be careful in writing the information they convey so as not to cause negative impacts in society. This research aims to reveal the writers' efforts to manage the information that will be conveyed to their readers through the works produced, as well as the moral responsibility that underlies the writers in conveying the writings they make. This research uses a qualitative method with a phenomenological approach. Data collection was conducted through interviews and observations with 8 Sundanese writers in Bandung City, as well as a review of documentation relevant to the research. The results showed that the writers interpreted their writing as a timeline marking the recording of expressions when the writing was produced. Its function is to see the development of the author's mindset and perspective on something he wrote. The moral responsibility that writers carry in the writing they produce, generally aims to maintain the possibility of negative influences from the writing they produce. The moral responsibility is not writing things that disturb society, inviting readers to do good and prevent bad, making writing as a work of writing that educates, informs and entertains, and does not damage, the philosophical truth of Sundanese history, benefits the ummah, keeps the words to be written so as not to poison the community, can accompany many people to grow together, and does not clash with SARA (Ethnicity, Religion, Race, and Intergroup).